Aplikas Pos (Point of Sale) Berbasis Desktop: Studi Kasus Dehenz Tol Soroja - Rijal, Ahmad; Senubekti, Mamok Andri; Anggraini, Novita (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Dehenz is a shop business established in the culinary sector which is quite popular in Soreang, Bandung Regency and has many buyers every day. Because we still use manual methods for recording, this really affects performance at Dehenz. In this case, buying and selling activities cannot be separated from the help of technology to make them more efficient. There are many facilities from the digital world that can be utilized in various business fields, one of which is a desktop-based cashier application, which is a solution for Dehenz which still uses manual methods in recording its sales. Thus, it is prone to human error, discrepancies, and data that is unsafe or easily lost/damaged. With this, the author aims to build a web-based cashier application as a form of action to overcome the owner's problems. The design method used in this research is an object-oriented method using the CodeIgniter 3 Framework. The aim of creating this web-based cashier application is to simplify the process of recording sales reports for servers or cashiers. It is anticipated that the desktop-based Point Of Sale application will increase efficiency and speed of recording product orders. Also has the ability to produce sales data quickly, precisely and accurately.